Herbal medicine for acute bronchitis: A qualitative interview study of patients' and health professionals' views. (December 2020) - Soilemezi, Dia; Leydon, Geraldine M.; Yan, Ruiyang; Simpson, Catherine; Bell, Margaret; Bostock, Jennifer; Moore, Michael; Willcox, Merlin
Highlights: Many patients in the UK are willing to try herbal medicine for acute bronchitis. Some patients were concerned about effectiveness, side-effects and cost of herbals. Some GPs were concerned that herbals could interact with conventional medicines. Most patients would trust the advice of their GP on herbal medicines. Most GPs would recommend herbal medicines if there are evidence-based guidelines. Abstract: Background: Antibiotics are widely prescribed for acute bronchitis in the UK. Herbal medicine could be used instead to provide symptom relief. Aim: To explore the views of patients and health professionals on using herbal medicine for acute bronchitis instead of antibiotics. Design and setting: This was a nested qualitative study, conducted alongside a feasibility randomised clinical trial which ran from July 2018 to May 2019 in 20 GP practices in Wessex, UK. Method: We conducted telephone semi-structured interviews with patients and with health professionals. The interview data were transcribed and analysed thematically. Results: Overall, 40 interviews were conducted with 29 patients, six GPs and five nurses. While some patients believed antibiotics are more effective, most were aware of resistance and were keen to try an alternative, including herbal medicine. Several patients believed herbals would be "less intrusive" than antibiotics, whereas a few disliked the taste or experienced side-effects after taking a herbal. Professionals were concerned about potential interactions with conventional medicines. Many patients trusted herbals because of their long history of use, while some did not understand them. Availability of herbals without a prescription enables patients to use them for self-care, but their cost was a barrier for some. Many patients were willing to take a herbal if advised by their GP. Most GPs were happy to recommend a herbal, if endorsed by evidence-based guidelines. Conclusion: Many patients and health professionals would consider using herbal medicine for acute bronchitis, if based on trustworthy advice and evidence-based guidelines respectively.